Agile processes in software engineering and extreme programming : 16th International Conference, XP 2015, Helsinki, Finland, May 25-29, 2015, Proceedings - Lassenius, Casper; Dingsoyr, Torgeir; Paasivaara, Maria (Lecture Notes in Business Information Processing, 2015)
This book contains the refereed proceedings of the 16th International Conference on Agile Software Development, XP 2015, held in Helsinki, Finland, in May 2015. While agile development has already become mainstream in industry, this field is still constantly evolving and  continues to spur an enormous interest both in industry and academia. The XP conference series has always played, and continues to play, an important role in connecting the academic and practitioner communities, providing a forum for both formal and informal sharing and development of ideas, experiences, and opinions. The theme of XP 2015 "Delivering Value: Moving from Cyclic to Continuous Value Delivery" reflects the modern trend towards organizations that are simultaneously very efficient and flexible in software development and delivery. The 15 full and 7 short papers accepted for XP 2015 were selected from 44 submissions. All of the submitted papers went through a rigorous peer-review process. Additionally, 11 experience reports were selected from 45 proposals, and in each case the authors were shepherded by an experienced researcher.